2018
DOI: 10.1159/000488121
|View full text |Cite
|
Sign up to set email alerts
|

Fabry Nephropathy: An Evidence-Based Narrative Review

Abstract: Fabry disease (FD) is a rare, X-linked disorder caused by mutations in the GLA gene encoding the enzyme α-galactosidase A. Complete or partial deficiency in this enzyme leads to intracellular accumulation of globotriaosylceramide (Gb3) and other glycosphingolipids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 113 publications
0
29
0
3
Order By: Relevance
“…Non-specific treatment includes angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) to maintain a urine protein to creatinine ratio less than 0,5 g/g. Some evidence also support the potential use of medications such as amiloride as podocyte stabilizator and antiproteinuric or paricalcitol 63 .…”
Section: Intracellular Deposit Storage Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Non-specific treatment includes angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) to maintain a urine protein to creatinine ratio less than 0,5 g/g. Some evidence also support the potential use of medications such as amiloride as podocyte stabilizator and antiproteinuric or paricalcitol 63 .…”
Section: Intracellular Deposit Storage Diseasesmentioning
confidence: 98%
“…It has been reported that podocyturia might be an earlier marker of disease than proteinuria, although microalbuminuria/proteinuria is the most commonly used method for kidney function assessment in early stages (first or second decade of life) 62 . Novel procedures to differentiate female AFD patients are proteomic analysis or urinary Gb3 or lyso-Gb3 determination 63 .…”
Section: Intracellular Deposit Storage Diseasesmentioning
confidence: 99%
“…The prevalence of this disease is estimated to be between 0.85 and 2.5 cases per 100,000 individuals worldwide, but it may be largely underestimated due to the wide spectrum of clinical phenotypes [2]. Indeed, FD is a multisystem pathology, involving renal, cardiovascular, neurological, dermatological, and ophthalmological systems [3], that, if untreated, leads to severe complications that may end in premature death [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…4 D–F). Both filtration and reabsorption dysfunction lead to end-stage renal disease, which requires hemodialysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%